Mental health and human rights: The experience of professionals in training with the use of mechanical restraints in Madrid, Spain - Luis Nocete Navarro; Víctor López de Loma Osorio; María Fe Bravo Ortiz; Alberto Fernández Liria (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
Mechanical restraint is a coercive procedure in psychiatry, which despite being permitted in Spain, raises significant ethical conflicts. Several studies argue that non-clinical factors - such as professionals' experiences and contextual influences - may play a more important role than clinical factors (diagnosis or symptoms) in determining how these measures are employed. The aim of this study is to understand how the experiences of mental health professionals in training relate to the use of mechanical restraints in Madrid's mental health network. Qualitative phenomenological research was conducted through focus groups in 2017. Interviews were transcribed for discussion and thematic analysis with Atlas.ti. Descriptive results suggest that these measures generate emotional distress and conflict with their role as caregivers. Our findings shed light on different factors related to their experiences and contexts that are important in understanding the use of mechanical restraint, as well as the contradictions of care in clinical practice.